Influence of Diffusion on Bio-chemical Reaction of the Morphogenesis Process - Sambath, M.; Balachandran, K. (Journal of Applied Nonlinear Dynamics, 2026)
This paper presents a mathematical strategy for exploring the dynamical behavior of bio-chemical model in temporal morphogenesis which is a generalization of the model studied by Gierer-Meinhardt. We here study the spatially homogeneous and non-homogeneous periodic solutions through all parameters of the system are spatially homogeneous. In order to verify our theoretical results, some numerical simulations are also carried out.